The use of OpenAlex to produce meaningful bibliometric global overlay maps of science on the individual, institutional, and national levels - Haunschild, Robin; Bornmann, Lutz (PloS one, 2024)
The Social Systems Citations Theory (SSCT) is the most recent theory of citations integrating previous theories. It focuses on communications in science that are formally manifested as publications and citations in scientific communication networks. These networks can be observed and empirically studied by using science maps. Science maps typically visualize networks of communication elements such as key words, cited references, and subject areas. In this study, a procedure to create global overlay maps using OpenAlex is proposed. It is an important advantage of OpenAlex publication and citation data that they are freely available. Overlay maps visualize how the overlaid data (e.g., research of an institution) are positioned in the whole science system (the base map). Six different base maps are provided to the user for their own applications. Using one of these base maps, example overlay maps for two individuals (the authors of this paper) and four research institutions are shown and discussed. A method for normalizing the overlay data is also proposed that can be used for the comparison of two different overlaid units. Overlay maps using raw overlay data display general concepts more pronounced than specific concepts. It is the other way around with their counterparts using normalized overlay data. Advantages and limitations of the proposed overlay approach based on OpenAlex are discussed.